A Study on the Demographic and Clinical Profile of Patients with Haemotoxic Snake Bite - Kalpana Ramanathan; Haridoss Sripriya Vasudevan (Asian Journal of Medical Research, 2019)
Background: In India, snake bite is an important medical emergency and reason for hospital admission. There is a predominance of haemotoxic bites in South India. Factors contributing to fatal snake bite include problems with dosage of antivenom, delay in treatment and failure to observe and treat complications. Objectives: To study the demographic and clinical profile, complications and outcome in patients with haemotoxic snake bite.Subjects and Methods:This was a hospital based observational study conducted in a tertiary government hospital for a period of one year. The clinical and demographic profile of patients with haemotoxic snake bite and factors contributing to poor outcome were studied. Statistical analysis: Mean, Standard deviation, Percentiles and frequency, Percentages for continuous and categorical data, Chi square test for association between proportions and p < 0.05 for statistical significance.Results:A total of 100 patients of haemotoxic snake bite were studied. The majority were male patients (63%) in the age group of 40-60 years. Most of the patients were farmers and labourers from a rural background. 92% of the patients were admitted within 6 hours of the bite. Local manifestations that were commonly seen were swelling of the bitten limb and tender lymphadenopathy. Bleeding manifestations were seen in 31%. The most common complication was acute kidney injury seen in 10%. Mortality rate was 3%.Conclusion: Factors contributing to poor outcome were duration between bite and admission and presence of acute kidney injury.